ANALISIS SEGMENTASI, PENENTUAN TARGET, DAN POSISI PASAR PADA AGROINDUSTRI SENDOK-GARPU BIODEGRADABLE - Fitri Nur Haerunnisa; Isna Aulia Syahdiar; Toibah Toibah; Annisa Islamiati; Salma Alif Nabilah; Dian Novitasari (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
A biodegradable spoon-fork is environmentally cutlery made from corncob waste. This product is a new beginning in the market to improve corncob waste value and reduce the incidence of plastic waste due to using single-use plastic spoons and forks. Biodegradable spoon-fork as a new product certainly requires an appropriate marketing strategy to accept the product in the market. Based on these problems, this study was due with the objectives of (1) analyzing the segmentation of biodegradable spoon-fork, (2) knowing the target of biodegradable spoon-fork, and (3) identifying the market position of biodegradable spoon-fork. Research data was collected by distributing online and offline questionnaires to 99 research respondents who were consumers of biodegradablespoon-fork. Data collection and analysis were collected for four months, from May to August 2021. The data was analyzed by Cluster Analysis and Biplot Analysis method. The results show three segments formed, where the selected target market is cluster two with the characteristics of respondents aged < 20 years, students/college with an expenditure level of < Rp 500,000. Biplot analysis provides positioning of the number of consumers' interest in buying biodegradable spoon-fork. Therefore cutlery is offered as an environmentally friendly product to reduce plastic cutlery waste.Keywords: biodegradable spoon-fork, positioning, segmentation, targeting